Interoceptive sensibility differentiates the predictive pattern of emotional reactivity on depression - Huang, Yun-Hsin; Huang, Yu-Ting; Yen, Nai-Shing (Frontiers in Psychology, 2023)
The role of emotional reactivity in the psychopathology of depression has been studied widely but not comprehensively. Inconsistencies in existing literature indicate the presence of other factors may affect this dynamic. An individual’s method of processing their physiological sensations is a third variable because emotions are psychophysiological. This study identified the predictiveness of ease of activation, intensity, and duration of negative and positive emotions on depressive symptoms differentiated by interoceptive sensibility (IS). A total of 270 community participants filled-in questionnaires assessing their IS, habitual emotional reactivity, depressive severity, and response bias. A two-step clustering analysis identified the IS characteristics. Negative and positive reactivity models among each IS cluster were tested using bootstrapping regression, controlling for gender and response bias. IS can be clustered into “high IS,” “low IS,” and “worriers.” Both positive and negative reactivity’s predictiveness patterns on depression were different between IS clusters. Lower positive reactivity predicted depression among individuals with low IS (harder to activate positive emotions) and worriers (shorter duration of positive emotions) but not among individuals with high IS. Those with high IS also exhibited the highest positive reactivity. Ease of activating negative emotions predicted depression among high IS individuals, and a longer duration of negative emotions predicted depression among worriers. IS may affect the psychopathology of depression through subjective emotional reactivity. Thus, IS characteristics can be incorporated into intervention plans.